Features, Frames and Fractions: Julián Ríos’s "Monstruario" - Olmos, Miguel A. (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Wordplay, puns and other playful ways of using language beyond its standard combining rules are the hallmarks of Julián Ríos’s work. Based on the analysis of Monstruary, this paper considers the methods Ríos uses to handle material and arrange it within several kinds of structures: frame stories, generic models (Künstlerroman), enunciative modalities (witness-narrator using non fictional forms of discourse), dialogic interactions between characters, intradiegetic continuity of art objets and their surrounding world, together with the widespread of fractals. The artistic issues dealt with by Monstruary lead to an apology of creative freedom as well as to witty exercices of literary criticism and satire, a perfect match for genuine ludic writings.
Keywords: literary field; criticism; dialog; ekphrasis; fractals; wordplay; literality; frame; counterfeit; Künstlerroman; satire